PENINGKATAN HASI BELAJAR IPS SISWA PADA MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI) - Baziduhu Laia (Institut Pendidikan Tapanuli Selatan, 2021)
This study aims to describe learning using the Problem Based Learning (PBI) model and increase student learning outcomes through the application of the Problem Based Learning (PBI) model. This research is a Classroom Action Research (PTK). The instruments used were (a) Teacher (Researcher) and Student Observation Sheet, (b) Interview Guide Sheet, (c) Documentation, (d) Field Notes, (e) Learning Outcomes Test. Research subjects, students of class IX SMP Negeri 3 Onolalu with a total of 20 students. The results of the research obtained indicate that the Instruction Problem Based Learning (PBI) model can improve student learning outcomes, especially in tube material. This is because applying the Problem Based Instruction (PBI) learning model of students who are more active in learning, better understand the concept of material well, are able to solve social science problems, students' analytical power on social studies problems increases, they are more critical in solving problems and group learning is carried out. make students more open in conveying their ideas. Based on the results of this study, it can be denied that using the Problem Based Learning Instruction (PBI) model can improve student learning outcomes, especially in tube material. The Problem Based Instruction (PBI) Learning Model can be used as an alternative in improving student learning outcomes in social science learning.